Publication Manual of the American Psychological Association. - American Psychological Association (Washington, DC : American Psychological Association, 2001)
The Publication Manual of the American Psychological Association is the style manual of choice for writers, editors, students, educators, and professionals in psychology, sociology, business, economics, nursing, social work, and justice administration, and other disciplines in which effective communication with words and data is fundamental. In addition to providing clear guidance on grammar, the mechanics of writing, and APA Style, the Publication Manual offers an authoritative and easy-to-use reference and citation system and comprehensive coverage of the treatment of numbers, metrication, statistical and mathematical data, tables, and figures for use in writing, reports, or presentations. The fifth edition has been revised and updated to include: a) the latest guidelines and examples for referencing electronic and online sources; b) new and revised guidelines for submitting papers electronically; c) Improved guidelines for avoiding plagiarism; d) Simplified formatting guidelines for writers using up-to-date word-processing software; e) all new guidelines for presenting case studies; f) improved guidelines for the construction of tables; g) updates on copyright and permissions issues for writers; h) new reference examples for audiovisual media and patents; and i) an expanded and improved index for quick and easy access.
Content and Organization of a Manuscript -- Expressing Ideas and Reducing Bias in Language -- APA Editorial Style -- Reference List -- Manuscript Preparation and Sample Papers to Be Submitted for Publication -- Material Other than Journal Articles -- Manuscript Acceptance and Production -- Journals Program of the American Psychological Association -- Appendix A: Checklist for Manuscript Submission -- Appendix B: Checklist for Transmitting Accepted Manuscripts for Electronic Production -- Appendix C: Ethical Standards for the Reporting and Publishing of Scientific Information -- Appendix D: References to Legal Materials -- Appendix E: Sample Cover Letter.
Includes bibliographical references (pages 363-377) and index.
Keywords: Psychology -- Authorship -- Style manuals; Social sciences -- Authorship -- Style manuals; Psychological literature -- Publishing -- Handbooks, manuals, etc; Social science literature -- Publishing -- Handbooks, manuals, etc